Thyroid and celiac disease in pediatric age: a literature review - Minelli, Roberta; Gaiani, Federica; Kayali, Stefano; Di Mario, Francesco; Fornaroli, Fabiola; Leandro, Gioacchino; Nouvenne, Antonio; Vincenzi, Francesca; de' Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
Chronic autoimmune thyroid disease or Hashimoto thyroiditis (HT) and Graves-Basedow disease (GD) are the main autoimmune thyroid diseases in pediatric age. Both are characterized by the production of anti-thyroid antibodies, by an infiltration of autoreactive B and T lymphocytes into the thyroid parenchyma and by alterations in thyroid function (hyperthyroidism in GD, normal function or subclinical hypothyroidism in HT with possible evolution towards manifest hypothyroidism). Celiac disease (CD) is a systemic autoimmune disease caused by gluten ingestion in genetically predisposed subjects, its prevalence is around 1% in Western Countries. It presents with a pathognomonic enteropathy, a variety of clinical manifestations, positivity for specific antibodies, positivity for typical haplotypes HLA DQ2/DQ8. The clinical manifestations may vary among four types: typical, atypical, silent and latent. Diagnosis can be made in presence of specific histopathologic findings in duodenal biopsies and antibodies positivity. Celiac disease is associated to various endocrine autoimmunities such as thyropathies, diabetes mellitus type 1, Addison disease, multiendocrine syndromes. The most frequent associated thyropaties are HT and GD. The present review aims to explore the associations between thyropathies and celiac disease in pediatric age.